Contextual similarity learning for image retrieval and classification: applications in person re-identification - Valem, Lucas Pascotti [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The exponential growth of image collections has demanded a significant increase in the use of machine learning and image retrieval applications across various scenarios. Despite the relevant advances, many methods still rely heavily on large volumes of labeled data for training, which establishes an important obstacle, once producing labeled data is generally expensive and time-consuming. To address this challenge, numerous techniques have been developed recently. A critical aspect of these approaches is effectively defining image similarity, which remains a central challenge in retrieval and machine learning applications, such as classification. The core of this issue is intrinsically linked to how information is represented and the methods used to compare these representations. A major limitation is that most of them still rely on pairwise measures, ignoring other meaningful information present in the neighborhood that can be used to further increase the results. This work focuses on improving the effectiveness of image retrieval by visual content and classification tasks using contextual similarity, moving beyond traditional pairwise measures to exploit relationships among elements. Contextual similarity learning is employed to capture underlying relationships among elements, using techniques such as rank-based models, contextual measures, graphs, and hypergraphs to model contextual information effectively. This dissertation proposes seven novel methods applied across general-purpose and person re-identification (Re-ID) scenarios addressing different contributions. Three main tasks were considered: query performance prediction, image retrieval, and image classification. A wide experimental evaluation was conducted, totaling 17 datasets and more than 50 visual image descriptors. The proposed methods, when compared with state-of-the-art and recent baselines, demonstrate results that are comparable to or surpass those of existing approaches in most cases.

O crescimento exponencial das coleções de imagens produziu um aumento significativo nas aplicações de aprendizado de máquina e recuperação de imagens em diversos cenários. Apesar dos avanços recentes, muitos métodos ainda dependem fortemente de grandes volumes de dados rotulados para treinamento, o que representa um obstáculo importante, uma vez que produzir dados rotulados é geralmente custoso. Para enfrentar esse desafio, várias técnicas foram desenvolvidas. Um aspecto crítico de tais abordagens é definir a similaridade entre imagens de maneira eficaz, o que continua sendo um desafio central em aplicações de recuperação e aprendizado de máquina, tais como classificação. A questão central está intrinsecamente relacionada à forma como a informação é representada e aos métodos usados para comparar essas representações. Uma grande limitação é que a maioria ainda depende de medidas par-a-par e ignoram outras informações significativas presentes na vizinhança que podem ser usadas para melhorar os resultados. Este trabalho foca em melhorar a eficácia da recuperação de imagens por conteúdo visual e tarefas de classificação usando similaridade contextual, indo além das métricas tradicionais par-a-par para explorar as relações entre os elementos. O aprendizado de similaridade contextual é empregado para explorar relações de vizinhança entre os elementos, usando técnicas tais como informações baseadas em ranqueamento, medidas contextuais, grafos e hipergrafos para modelar a informação contextual de forma eficaz. Esta tese propõe sete métodos novos aplicados a cenários de propósito geral e re-identificação de pessoas (Re-ID) abordando diferentes contribuições. Três tarefas principais foram consideradas: estimativa de eficácia de consultas, recuperação e classificação de imagens. Foi realizada uma ampla avaliação experimental, totalizando 17 coleções de imagens e mais de 50 descritores visuais. Os métodos propostos, quando comparados com o estado-da-arte, demonstram resultados que são comparáveis ou superiores aos das abordagens existentes na maioria dos casos.
Aprendizado de similaridade contextual para recuperação e classificação: aplicações em re-identificações de pessoas
Keywords: Contextual similarity information; Image retrieval; Image classification; Query performance prediction; Person re-id; Representation learning; Similaridade contextual; Recuperação de imagens; Classificação de imagens; Estimativas de eficácia; Re-identificação de pessoas; Aprendizado de representações